1947
DOI: 10.1017/s0022172400013929
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and control ofSalmonella thompsoninfection of fowls

Abstract: The details are given of the epidemiology ofS. thompsoninfection in a flock of pullets which survived an outbreak of this disease when chicks, and also of a flock of adult birds suspected of being carriers of the organism. The results of blood testing and bacteriological examinations of cloacal swabs, random faecal samples and eggs from both flocks indicated that:(1) Many chicks which survived an outbreak ofS. thompsoncontinued to carry the organism for some months without showing any symptoms. In most cases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1952
1952
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 31 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…In this respect it differs from S. thompson (10), S. anatum (11) but behaves in a manner similar to S. pullorum (10) and S. menston (12).…”
Section: Discussionmentioning
confidence: 84%
“…In this respect it differs from S. thompson (10), S. anatum (11) but behaves in a manner similar to S. pullorum (10) and S. menston (12).…”
Section: Discussionmentioning
confidence: 84%
“…Its presence in the former site is presumably as a result of infection of the ovary while contamination of the albumen may result from infection of the upper oviduct. Contamination of egg shells with salmonellas is usually thought to be the result of faecal carriage [10]. While this, or the environment, could clearly have been the source in the study reported here, the apparent lack of relationship between presence of S. enteritidis PT4 in faeces and on egg shells with the SPF-I birds (Table 1) raises other possibilities.…”
mentioning
confidence: 73%
“…typhi murium over a period of 65 days by naturally infected adult turkeys and up to 15 days in artificially infected adult turkeys. found that poults voided typhimurium in feces up to 96 days after oral admini stration, and they indicated that disease transmission resulted when this fecal material was ingested by susceptible poults, Buxton and Gordon (1947) observed that chickens may remain intestinal carriers of £, thoirpson up to 18 months. Wilson (1948) found that adult chickens may serve as intestinal carriers of typhimurium and thompson for periods up to 9-16 months.…”
Section: Modes Of Transmission Of Salmoneilae To Turkeys Prior To Slamentioning
confidence: 99%
“…all strains penetrated the shell membranes and multiplied within the eggs to populations as high as one billion cells per ml of egg meat (Stokes et al 1956), Penetration and growth occurred as rapidly with nonmotile serotypes as with motile serotypes, Williams (1959) stated that Salmonellae are able to gain entrance into the egg, to multiply in the yolk, and to infect the developing embryo which may die or hatch as an infected poult, Buxton and Gordon (1947), Gregory (1948), Lancaster and Crabb (1953), and Banwart and Ayres (1957 have shown that egg albumen has very little inhibitory effect on Salmonellae that penetrate the shell, Wilson (1948) cautioned that mixing contaminated eggs with clean eggs in the incubator is a means of spreading infection. Proper tem perature and moisture has been shown to be important in the rate of penetration through the shell.…”
Section: Eggsmentioning
confidence: 99%
See 1 more Smart Citation